If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) = -4(x + 5) Reorder the terms: 2(3 + x) = -4(x + 5) (3 * 2 + x * 2) = -4(x + 5) (6 + 2x) = -4(x + 5) Reorder the terms: 6 + 2x = -4(5 + x) 6 + 2x = (5 * -4 + x * -4) 6 + 2x = (-20 + -4x) Solving 6 + 2x = -20 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + 2x + 4x = -20 + -4x + 4x Combine like terms: 2x + 4x = 6x 6 + 6x = -20 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + 6x = -20 + 0 6 + 6x = -20 Add '-6' to each side of the equation. 6 + -6 + 6x = -20 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = -20 + -6 6x = -20 + -6 Combine like terms: -20 + -6 = -26 6x = -26 Divide each side by '6'. x = -4.333333333 Simplifying x = -4.333333333
| 8z^2-68z=32 | | 576/x=0 | | 3x-8+7x=12+9x-3 | | 3x^3y^2+5xy^4=0 | | X-1/-3=x-5/-2 | | 49=x+17 | | 3/14/7/12 | | 16m=1/9 | | 16-c=34 | | x+7+2x=13-4x | | 21=3m-6 | | x/3-2/3=x/4+1/4 | | x-28=-3x+12 | | (X-5)/-2=(x-1)/-3 | | (3+r)=3+4 | | 5(x-1)=5(x+5)-15 | | 7(x)-6=45 | | -20+4x=6x-30 | | 4x+2(1/2x-5)=0 | | 9y-10=53 | | X-5/-2=x-1/3 | | 1/9=16m | | 6x-15=5x-12 | | x^3+x^2-6x=61 | | 3(a-1)=4(a-15) | | -15-x=12 | | r-6r=-1 | | 4x-4=3x+4.5 | | 5a+a=6a | | 3x/5-1=14 | | 7/2x+2=3x+6 | | 1/2(2x^2-8x+16)^-1/2*(4x-8) |